MENINGKATKAN KUALITAS PENDIDIKAN: PROBLEM SISWA DI SDN 75 KOTA BENGKULU DAN SOLUSINYA - Saputri, Marda Herdiana; Napiah, Salma; Setiawan, Muchlis Fajar (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
Quality education is the key to producing an intelligent and competent generation. However, at SDN 75 Bengkulu City, there are still several problems that hinder improving the quality of education, such as low student learning motivation, limited facilities, and lack of variation in teaching methods. This study aims to identify the problems faced by students at SDN 75 Bengkulu City and find solutions to improve the quality of education at the school. The method used is a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation studies. The study results indicate that low student motivation is caused by a lack of parental support and monotonous learning methods. In addition, limited facilities such as classrooms and teaching materials are also obstacles to learning. The proposed solutions include the development of innovative learning methods, improving educational facilities, and empowering parents. With these steps, it is hoped that the quality of education at SDN 75 Bengkulu City can improve significantly.